Gelatine and genetically modified food (GMF) / Nur Athirah Mohd Fauzi … [et al.] - Mohd Fauzi, Nur Athirah; Mohd Jalani, Nursolehah; Mohd Rashdi, Nurul Iffah Atiyah; Roslan, Ruhil Farhanim (2023)
Gelatine, a by-product of animal origin, is obtained from partially hydrolyzed collagen tissue found in various parts of animals, serving as a food ingredient for stabilization, foaming, emulsifying, and other purposes. Countries such as Malaysia, Indonesia, and some Muslim countries demand halal gelatine in both imported and domestically produced products. Gelatine is a substance used in the food and medicine industry due to its unique properties, with its use dating back centuries. Its applications have expanded into the pharmaceutical, cosmetic, and technical industries. Without gelatine, certain products are difficult to produce.